Data Rescue : defining a comprehensive workflow that includes the roles and responsibilities of the research library - Bothma, T.J.D. (Theodorus Jan Daniel) (University of Pretoria, 2023)
Thesis (PhD (Research))--University of Pretoria, 2023.